Technical and economic aspects of revitalization of down-town tenement-houses in Wrocław - Marcinkowska, Ewa; Gawron, Krzysztof; Rejment, Mariusz (Journal of Civil Engineering and Management, 2015)
In the paper the authors examined the relations between the physical deterioration degree and the price of the tenement-houses in Wrocław. The researches concern the year’s 1991–2009. According to the following analyses: technical, technical-economic (concerning the relations between buildings technical condition and buildings price) and economic the authors have come the conclusions concerning the sensibility of the revitalization work. The authors also estimated the purchase limit profitability of the tenement-houses, which are going to be repaired and modernized or to be demolished and next to be built a new tenement-house. The direction of the engineering activities was shown. They could improve the economic effectiveness of the revitalized tenement-houses.